2022
DOI: 10.1038/s41598-022-06599-5
|View full text |Cite
|
Sign up to set email alerts
|

Exploration of autoantibody responses in canine diabetes using protein arrays

Abstract: Canine diabetes has been considered a potential model of human type 1 diabetes (T1D), however the detection of autoantibodies common in humans with T1D in affected dogs is inconsistent. The aim of this study was to compare autoantibody responses in diabetic and healthy control dogs using a novel nucleic acid programmable protein array (NAPPA) platform. We performed a cross-sectional study of autoantibody profiles of 30 diabetic and 30 healthy control dogs of various breeds. Seventeen hundred human proteins rel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 31 publications
0
6
1
Order By: Relevance
“…As reported for laboratory mice and human diabetic subjects, CDM dogs had significantly (p < 0.0001) increased Th40 cell numbers ( Figure 4A ). Unlike the reports for variable and highly inconsistent levels of autoantibodies in CDM ( 3 , 9 ) Th40 cells were universally increased in CDM. PBMC were analyzed for CD3 and then CD4 + CD40 + within the CD3 gated subset ( Figure 4A for controls and 4B for CDM).…”
Section: Resultscontrasting
confidence: 93%
See 3 more Smart Citations
“…As reported for laboratory mice and human diabetic subjects, CDM dogs had significantly (p < 0.0001) increased Th40 cell numbers ( Figure 4A ). Unlike the reports for variable and highly inconsistent levels of autoantibodies in CDM ( 3 , 9 ) Th40 cells were universally increased in CDM. PBMC were analyzed for CD3 and then CD4 + CD40 + within the CD3 gated subset ( Figure 4A for controls and 4B for CDM).…”
Section: Resultscontrasting
confidence: 93%
“…In human disease, GAD and IA-2 auto antibodies are associated with LADA ( 37 ). An exploration of Aab comparing 30 healthy controls and 30 CDM dogs found that at a specificity of 90%, six autoantibodies had sensitivity greater than 10% ( 9 ). To attempt to address the lack of Aab in CDM a novel array technique that queried 1700 pancreatic proteins was only able to identify 6 autoantibodies with sensitivity greater than 10% ( 9 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Furthermore, the findings of the current study were inconsistent with those of other rodent studies, which reported lowered glucose levels and decreased DM complications after treatment with A. paniculata and andrographolide ( Yu et al, 2003 ; Lee et al, 2010 ; Nugroho et al, 2012 ; Ji et al, 2016 ; Islam, 2017 ; Naik et al, 2017 ; Wediasari et al, 2020 ; Mehta et al, 2021 ; Syukri et al, 2021 ). However, the DM in rodents was chemically induced with streptozotocin or alloxan, which promotes cell death and decreases insulin production; this is different from the canine DM produced by chronic autoantibody destruction over a long period ( Al-awar et al, 2016 ; Furman, 2021 ; O’Kell et al, 2022 ). A. paniculata treatment was reported to lead to beneficial outcomes in insulin-resistant obese mice, a model for type 2 diabetes (T2DM), which is not frequent in dogs ( Catchpole et al, 2005 ; Akhtar et al, 2016 ; Heydemann, 2016 ; Chen et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%